Guild-Ridden Labor Markets : The Curious Case of Occupational Licensing - Kleiner, Morris M.; Project Muse. (Kalamazoo, Michigan : W.E. Upjohn Institute for Employment Research, 2015)
Kleiner examines why the institution of occupational licensing has had such a curious evolution and influence in the United States, the European Union, and China. He also discusses the many similarities it has to guilds.
Title page; Copyright page; Contents; Acknowledgements; Chapter1 -- Anatomy of Occupational Licensing; Chapter 2 -- The Evolution of Occupational Licensing; Chapter 3 -- The Costs, Mobility, and Quality of Occupational Licensing Services; Chapter 4 -- Battles among Licensed Occupations; Chapter 5 -- Occupational Licensing in Different Institutional and International Contexts; Chapter 6 -- Policy Implications of the Evolution of Occupational Licensing in the United States and Elsewhere; References; Author; Index; About the Institute
Description based on print version record.
Keywords: Professions -- Licenses; Occupations -- Licenses; Guilds; Guilds -- History; Professions -- Licenses -- History; Occupations -- Licenses -- History; History; Electronic books